First isolation and characterization of SARS-CoV-2 from COVID-19 patient of North East India - Aniruddha Jakharia; Biswajyoti Borkakoty; Sumi Pait; Gautam Baruah; Rahul Hazarika; Dipankar Biswas (Indian Journal of Pathology and Microbiology)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) responsible for the current pandemic has resulted in over 5 million deaths globally. More than a year has passed, still SARS-CoV-2 panic the public life. Virus isolation is of paramount importance for development of vaccines, in-vitro screening of antiviral compounds, pathogenesis studies, etc., Many cell lines were studied for amplification and replication of SARS-CoV-2 and Vero cells were found to be ideal cell lines for isolation. In May 2020, ICMR-Regional Medical Research Centre, NE region, India, successfully established the SARS-CoV-2 culture system in Vero CCL-81 cell lines. Phylogenetic analyses of the whole genome sequences of the SARS-CoV-2 isolate (EPI_ISL_2501532 | 2020-05-19) showed monophyletic clade G and lineage B.1.1.